The confidence effects of fiscal consolidations. (30th July 2015) - Beetsma, Roel; Cimadomo, Jacopo; Furtuna, Oana; Giuliodori, Massimo
Abstract: We explore how fiscal consolidations affect private sector confidence, a possible channel for the transmission of fiscal policy that has received particular attention recently as a result of governments embarking on austerity trajectories in the aftermath of the crisis. Panel regressions based on the annual action-based datasets of Devries et al. (2011) and Alesina et al. (2014a) show that consolidations, and in particular their unanticipated components, affect confidence negatively. To obtain a more accurate picture of how consolidations affect confidence, we construct a monthly dataset of consolidation announcements, so that we can investigate the confidence effects in real time using an event study. The results suggest that consumer confidence falls around announcements of consolidation measures, an effect likely driven by revenue-based measures. Moreover, these effects are highly relevant for European countries with weak institutional arrangements, as measured by the tightness of fiscal rules or budgetary transparency. The effects on producer confidence are generally similar, but weaker than for consumer confidence. Long-term interest rates, as a measure of confidence in the sovereign, tend to fall around spending-based consolidation announcements. We have no evidence that the confidence effects of consolidation announcements are worse in slumps than in booms. Generally, strengthening institutional arrangements may help in mitigating adverse confidence effects of consolidations.